2006
DOI: 10.1242/dev.02189
|View full text |Cite
|
Sign up to set email alerts
|

Target-dependent specification of the neurotransmitter phenotype:cholinergic differentiation of sympathetic neurons is mediated in vivo by gp130 signaling

Abstract: Sympathetic neurons are generated through a succession of differentiation steps that initially lead to noradrenergic neurons innervating different peripheral target tissues. Specific targets, like sweat glands in rodent footpads, induce a change from noradrenergic to cholinergic transmitter phenotype. Here, we show that cytokines acting through the gp130 receptor are present in sweat glands. Selective elimination of the gp130 receptor in sympathetic neurons prevents the acquisition of cholinergic and peptiderg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
138
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(142 citation statements)
references
References 80 publications
(90 reference statements)
4
138
0
Order By: Relevance
“…Some neurons in rodent sympathetic ganglia are known to acquire cholinergic properties before birth at early embryonic stages Huber and Ernsberger, 2006). Studies in mice deficient for gp130, LIFR␤ (LIF receptor ␤), or CNTFR (CNTF receptor) have demonstrated that the embryonic cholinergic differentiation is not controlled by gp130 cytokines (Stanke et al, 2000(Stanke et al, , 2006. Consistently, our results show a lack of Satb2 expression during late embryonic or early postnatal stages.…”
Section: Satb2 Expression In the Rat Stellate Ganglionsupporting
confidence: 85%
See 1 more Smart Citation
“…Some neurons in rodent sympathetic ganglia are known to acquire cholinergic properties before birth at early embryonic stages Huber and Ernsberger, 2006). Studies in mice deficient for gp130, LIFR␤ (LIF receptor ␤), or CNTFR (CNTF receptor) have demonstrated that the embryonic cholinergic differentiation is not controlled by gp130 cytokines (Stanke et al, 2000(Stanke et al, , 2006. Consistently, our results show a lack of Satb2 expression during late embryonic or early postnatal stages.…”
Section: Satb2 Expression In the Rat Stellate Ganglionsupporting
confidence: 85%
“…This neurotransmitter plasticity occurs at postnatal stages in individual postmitotic neurons under the influence of neuropoietic cytokines, released by the target tissue after innervation (Landis, 1990(Landis, , 1996Stanke et al, 2006). The noradrenergic-to-cholinergic neurotransmitter switch can be induced in vitro in cultured sympathetic neurons by members of the neuropoietic cytokine family, such as ciliary neurotrophic factor (CNTF) or leukemia inhibitory factor (LIF) (Fann and Patterson, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Mice containing deletions in Bmpr1a or Smad4 in sympathetic neurons were obtained by crossing conditional lines to the DbhiCre (Stanke et al, 2006;Parlato et al, 2007) mouse line.…”
Section: Methodsmentioning
confidence: 99%
“…The Bmpr1a cKO and Bmpr1a cKO /1b ⌬ lines are in a mixed C57BL/ 6129SvEv genetic background (Yi et al, 2000;Parlato et al, 2007) with low 129SvEv contribution (Y. Mishina, personal communication). Smad4 ϩ/fl (Yang et al, 2002) are in a C57BL/6FVN mixed background and were repeatedly crossed with the DbhiCre line (C57BL6) (Stanke et al, 2006;Parlato et al, 2007) . Cell culture.…”
Section: Bmpr1bmentioning
confidence: 99%
See 1 more Smart Citation